Pareto and the Ambivalence of Emotions - Susca, Emanuela (Italian Sociological Review, 2024)
In the context of the growing interest in emotions in sociology, this article focuses on Pareto’s investigation of the emotional foundations of society. Firstly, this paper highlights that the Treatise on General Sociology offers two interpretative options: the first reiterates ideas already expressed before the Treatise and the second is profoundly original and focuses on residues. Accordingly, through an in-depth analysis of the theoretical framework of residues, this contribution highlights the originality and topicality of the Paretian approach. The conceptual framework of residues informs the understanding of the ambivalence of emotions in terms of their rich nuances, contradictions, and possible manifestations. Moreover, Pareto questions the accepted dichotomy between rationality and irrationality and shows how human action eludes rigid categorisation. Finally, employing a proudly elitist perspective that differs from today’s democracy-focused perspective, Pareto is a visionary in his acknowledgment of the importance of emotions in leadership and public opinion. The concluding remarks reflect on an aspect of the Paretian approach that seems less topical: the idea that humans want to hide their emotions from themselves and others.